Biopolitical bordering: Enacting populations as intelligible objects of government. (November 2020) - Scheel, Stephan
Since Foucault introduced the notion of biopolitics, it has been fiercely debated—usually in highly generalized terms—how to interpret and use this concept. This article argues that these discussions need to be situated, as biopolitics have features that do not travel from one site to the next. This becomes apparent if we attend to an aspect of biopolitics that has only received scant attention so far: the knowledge practices required to constitute populations as intelligible objects of government. To illustrate this point, the article focuses on processes of biopolitical bordering: the delineation of the target population that is to be known via statistical practices. Drawing on the example of Estonia I show that methodological decisions involved in this work have important biopolitical implications as they affect the size and composition of the population, thus shaping the design of programmes of government aiming at its regulation.